V-Band fade dynamics characteristics analysis in tropical region - Badron, Khairayu; Ismail, Ahmad Fadzil; Din, Jafri; Abdul Rahman, Tharek (Science Publications, 2010)
Problem statement: Satellite operations at V band in tropical and equatorial regions are constrained as a result of attenuation from rain. Approach: Statistics for 20 consecutive months of V band terrestrial link signal attenuation measurements in Malaysia were presented in this analysis. Such information was considered very pertinent for Earth-space communication link design and can be used for initial groundwork plan for the engineers as well as researchers. Results: The measured statistics were then fittingly scaled up to fit Earth-satellite link. The statistics were then broken down to examine diurnal variations. Characteristics of rain events such as fade duration and inter-fade interval were presented. Conclusion/Recommendations: It is essential to identify such characteristics for the design and implementation of future fade countermeasure techniques on satellite links.